SOCIALIZATION ACTIVITIES ON THE USE OF ORGANIC WASTE (RICE HUSKS, CORN HUSK WASTE, AND COCONUT SHELLS) INTO ENVIRONMENTALLY FRIENDLY ORGANIC COLOR PIGMENTS IN MAKING MARKER INK AT SMP NEGERI B. SRIKATON - Mu'awiyatu Al-laitsi; Solina Balqis; Lia Aseptin Murdini (Jurnal Abdisci, 2024)
Making marker ink from organic waste is one way to reduce the amount of waste that goes to landfills. Students will learn that organic waste can be reutilized into useful products. The process of making marker ink from organic waste involves innovation and creativity in creating solutions to environmental problems. This socialization can encourage students to think critically and find alternative solutions to everyday problems. This implementation activity involves lecturers and heads of study programs in the Bioengineering study program of the Muhammadiyah Sumatra Institute of Technology. The place and time of the activity at B. Srikaton State Junior High School, on October 14, 2024. This socialization activity consists of material delivery, discussion, making markers using organic materials, evaluation, and closing. We hope that this knowledge will encourage participants to care more about their surroundings and take small steps to reduce waste and make creative use of it.